Impact of school closures on the health and well-being of primary school children in Wales UK: a routine data linkage study using the HAPPEN Survey (2018–2020) - Michaela James (BMJ Open, 2021)
Objectives: This study aimed to explore the relationship between initial school closures and children’s health by comparing health and well-being outcomes collected during school closures (April–June 2020) via HAPPEN (the Health and Attainment of Pupils in a Primary Education Network) with data from the same period in 2019 and 2018 via the HAPPEN Survey. Setting: The study was conducted online with 161 primary schools across Wales involved in the ‘HAPPEN At Home’ Survey. Participants: Data were collected via the ‘HAPPEN At Home’ Survey capturing the typical health behaviours of children aged 8–11 years from 1333 participants across Wales. These data were compared with data in 2018 and 2019 also collected between April and June, from HAPPEN (2019 (n=1150) and 2018 (n=475)). Primary and secondary outcome measures: Primary outcomes included validated measures of physical activity, screen time, diet and dental health, as well as well-being, competency and autonomy. Free school meal (FSM) status was used as a proxy for socioeconomic deprivation. Analyses were repeated stratifying by FSM. Results: Comparing responses between April–June in 2020 (n=1068), 2019 (n=1150) and 2018 (n=475), there were improvements in physical activity levels, sleep time, happiness and general well-being for children during school closures compared with previous years. However, children on FSM ate fewer fruits and vegetables (21% less at five or more portions of fruits and vegetables (95% CI: 5.7% to 37%)) and had lower self-assessed school competence compared with 2019. Compared with those not on FSM, they also spent less time doing physical activity (13.03%, 95% CI: 3.3% to 21.7%) and consumed more takeaways (16.3%, 95% CI: 2% to 30%) during school closures. Conclusions: This study suggests that schools are important in reducing inequalities in physical health. The physical health (eg, physical activity and diet) of children eligible for FSM may be affected by prolonged school closures.